Les îles (2011) d’Isabelle Panneton et l’héritage de Philippe Boesmans : généalogie d’une démarche compositionnelle - Brasset, Marie-Pierre (Circuit : musiques contemporaines, 2021)
Dans les années 1980, après ses études auprès de Gilles Tremblay, Isabelle Panneton fait la rencontre de Philippe Boesmans lors d’un passage du compositeur belge à Montréal. Impressionnée par sa musique, elle se rendra en Belgique pour y suivre des leçons de composition avec lui de 1984 à 1987. Cette période sera déterminante pour la compositrice, ouvrant toute grande la porte à l’émergence de sa personnalité musicale. Ce texte retrace les moments forts du passage d’Isabelle Panneton chez le compositeur belge et met en lumière les liens qui les unissent, en guise de prélude à l’analyse de son trio Les îles pour violon, violoncelle et piano.
Keywords: Belgique; Belgium; Isabelle Panneton; Philippe Boesmans; chamber music; développement motivique; motivic development; musique de chambre

Lise Vachon and “Octobre au mois de mai”: Relistening to the Québécois Revolution - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

Marie-Claire Séguin: Feminism and Settler Colonialism in “Mater Maria” - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

"If you see me walking alone on the road": Sephardic Songs of Exile, Expulsion, Memory – and Return - Cohen, Judith R. (Armenian and Jewish Experience between Expulsion and Destruction, 2021)

Entretien avec Blxck Cxsper - Danjé, Michaëla (Afrotrans. Perspectives, entretiens, poésie, fiction, 2021)
"Dans cet ouvrage collectif, la parole est donnée exclusivement à des personnes trans noires, vivant en France pour la grande majorité. Ce recueil coordonné par Michaëla Danjé, femme trans membre et co-fondatrice de Cases Rebelles, contient des essais, de la fiction, de la poésie, des interviews, etc. Ce livre est constitué d'une multiplicité de voix, de perspectives et d'expériences diverses. Différentes générations sont également représentées. AfroTrans est beau, complexe, riche de lumière, d'amour et de force! "--Goodreads.com

Gabriel Dharmoo + Followup - Dharmoo, Gabriel (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Black Women Dancers, Jazz Culture, and “Show Biz”: Recentering Afro-Culture and Reclaiming Dancing Black Bodies in Montréal, 1920s–1950s - Jabouin, Emilie (Canadian Journal of History, 2021)
The documentary Show Girls, directed by Meilan Lam, makes an unprecedented contribution to the history of jazz and Black women jazz dancers in Montréal, Quebec, and to the conversation of jazz in Canada. Show Girls offers a glimpse into the lives of three Black women dancers of the 1920s–1950s. This essay asks what the lives of Black women dancers were like and how they navigated their career paths in terms of social and economic opportunities and barriers. I seek to better understand three points: (1) the gap in the study of jazz that generally excludes and/or separates dance and singing from the music; (2) the use of dance as a way to commercialize, sell, and give visual and conceptual meaning to jazz; (3) the importance of the Black body and the role of what I would define as “Afro- culture” in producing the ingenious and creative genre of jazz. My study suggests there is a dominant narrative of jazz, at least in academic literature, that celebrates one dimension of jazz as it was advertised in show business, and that bringing in additional components of jazz provides a counternarrative, but also a restorative, whole and more authentic story of jazz and its origins. More specifically, by re- exploring jazz as a whole culture that relies on music, song, and dance, this essay explores three major ideas. First, Black women dancers played a significant role in the success of jazz shows. Second, they articulated stories of self, freedom, and the identity of the New Negro through jazz culture and dance. Third, Black women’s bodies and art were later crystallized into images that further served to sell jazz as a product of show business.

Dick Montgomery et la personnification féminine afrodescendante en Amérique du Nord, 1935-1960 - Jacques, Raphaël (Histoire Engagée, 2021)

Socialisation musicale et sociabilités urbaines. Parcours de personnes immigrantes originaires d'Afrique du Nord à Montréal - Marcoux-Gendron, Caroline (L'interculturel contemporain au carrefour des disciplines, 2021)

Socialisation musicale, frontières culturelles et sociabilités urbaines. Les parcours des personnes immigrantes d'origine maghrébine à Montréal - Marcoux-Gendron, Caroline (Institut national de la recherche scientifique, 2021)

Avant-propos. Björk, Montréal et le Nunavut - McKinley, Maxime (Circuit : musiques contemporaines, 2021)
An article from Circuit, on Érudit.